Clinico-Pathological Study of Carcinoma Breast in Srikakulam District - Kiran, N. Ravi; Sowjanya, J. (RA Journal Of Applied Research, 2018)
Breast cancer is the most common site specific cancer in women and is the leading cause of death from cancer for women .The aim is to study the incidence and stage of presentation of breast carcinoma in the population factors with the Stage of Breast Carcinoma. To correlate the clinical findings with FNAC (positive or negative) reports and post operative histopathology reports. To determine Positive Predictive Value of FNAC with respect to the Post operative Histopathology Reports. Early breast carcinomas are well treated with simple mastectomy and axillary clearance while Locally advanced breast carcinomas (LABC) are treated well with a multidisciplinary approach of mastectomy with axillary clearance with chemotherapy and radiotherapy and in selected cases hormonal therapy.